Penerapan Sistem Informasi Manajemen di Sekolah untuk Meningkatkan Efisiensi Administrasi dan Pembelajaran - Kristanti, Tatik; Ramadhan Putra, Heldy (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This study aims to explore the impact of the implementation of the Management Information System (SIM) in schools in order to improve administrative efficiency and learning quality. The research method used is qualitative descriptive by collecting data through interviews, observations, and document analysis from schools that have implemented driver's licenses. The results of the study show that the implementation of SIM is able to reduce the workload of teachers by up to 30% and reduce errors in data processing by up to 50%. The SIM also speeds up the administrative process, allowing teachers to focus more on teaching and interacting with students. However, the study also found several challenges, such as limited technological infrastructure in remote areas and lack of training for teachers in using driver's licenses. The study concludes that the comprehensive implementation of driver's licenses, with adequate infrastructure support and training for teachers, can have a significant positive impact on improving the quality of education in Indonesia. A wider and more equitable implementation of SIM is urgently needed to ensure that all schools can experience the benefits of this technology.